2023
DOI: 10.3390/universe9050225
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Lorentz Invariance Violation via Gravitational Lensing and Analytical Eigenmodes of Perturbed Slowly Rotating Bumblebee Black Holes

Abstract: The ability of bumblebee gravity models to explain dark energy, which is the phenomenon responsible for the universe’s observed accelerated expansion, is one of their most significant applications. An effect that causes faster expansion can be linked to how much the Lorentz symmetry of our universe is violated. Moreover, since we do not know what generates dark energy, the bumblebee gravity theory seems highly plausible. By utilizing the physical changes happening around a rotating bumblebee black hole (RBBH),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…The shadow cast by a dyon BH, also known as Kerr-Newman-Kasuya spacetime, was studied in [42], where it was concluded that the shadow image is affected by both its rotational momentum and dyon charge. Övgün et al studied [43,44] the DA for spacetime solutions, such as the generalized Einstein-Cartan-Kibble-Sciama and null aether theories, using the GBT and verified that weak deflection of BHs is effected in these theories. An extensive review of quasinormal modes, analytic greybody factors, and gravitational lensing in rotating BH spacetime, such as bumblebees, is presented in [45].…”
Section: Introductionmentioning
confidence: 99%
“…The shadow cast by a dyon BH, also known as Kerr-Newman-Kasuya spacetime, was studied in [42], where it was concluded that the shadow image is affected by both its rotational momentum and dyon charge. Övgün et al studied [43,44] the DA for spacetime solutions, such as the generalized Einstein-Cartan-Kibble-Sciama and null aether theories, using the GBT and verified that weak deflection of BHs is effected in these theories. An extensive review of quasinormal modes, analytic greybody factors, and gravitational lensing in rotating BH spacetime, such as bumblebees, is presented in [45].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, a large amount of work has been implemented extensively to study gravitational lensing in recent years [69][70][71][72][73][74][75][76][77][78][79]. Furthermore, the gravitational lensing effects were considered powerful tools for testing the Weyl and bumblebee theories of gravity as well as the Lorentz invariance violation in bumblebee gravity [80,81]. It should be also noted that there exist investigations that added valuable contributions to understand deeply BH properties and gravitational lensing in the context of modified gravity and quintessence scalar fields: see, for example, [82][83][84].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, Lorentz-breaking modified field theory models are being extensively investigated. A series of meaningful studies have been conducted on the modification effects caused by Lorentz-breaking theories from flat spacetime to curved spacetime [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. In the relevant research papers, modifications are discussed at both the classical and quantum levels [17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%